Beach fale tourism in Samoa: The value of indigenous ownership and control over tourism - Scheyvens, Regina (Massey University, 2009)
This working paper reports on the findings of a research project which explores the budget tourism sector in Samoa as epitomized by beach fale tourism. Its main aim is to draw attention to the legitimacy and value of this often overlooked sector of the tourism market. As such it documents ways in which beach fale have contributed to development in Samoan villages, as well as identifying constraints to improvement of this sector. It concludes with a number of recommendations as to how sustainable, equity-enhancing development of tourism in Samoa can be supported in the future. Readers seeking a thorough understanding of beach fale tourism, including contextual information on the nature of tourism development in Samoa, and specific information concerning training and financial support for beach fale operators and impressions of tourists, are referred to an earlier paper in this series (CIGAD Working Paper No.3/2005 – see Scheyvens 2005b). The beach fale industry has contributed significantly to the development of a number of Samoan villages. There have been widespread multiplier effects for village communities as the fale are constructed using mainly local materials and expertise, and their owners often purchase items such as fruit, vegetables, seafood, and mats from the village and hire village labour during busy periods. Guests also contribute to the wider village through various means such as purchases made from village shops, use of local transport, and contributions to the collection plate when they attend a church service. Another benefit of beach fale tourism which has not been officially acknowledged is that it has restored the pride of many villagers in their home environment. Most Samoans feel genuinely honoured when people from all over the world come to visit their village and learn about their culture, and consequently community members contribute enthusiastically to village beautification efforts. Furthermore, the economic rejuvenation of some villages through beach fale tourism has reduced rural-urban migration as young people feel they now can stay in their home village and have a viable future. Despite the significant growth of the beach fale sector and the benefits this has brought to rural communities, it has been overlooked, disregarded, and in some cases harshly criticised by various commentators. Beach fale are seemingly invisible to those estimating the number of beds available for tourists in Samoa, for example, as they do not include beach fale accommodation in their estimates. Similarly, an Asian Development Bank report on Samoa (ADB 2000) with an entire chapter on tourism does not mention that beach fale exist. Outside consultants and investors, meanwhile, have voiced frustration with the communal land tenure system and its requirement for consensus in decisions concerning land use, as this has impeded the development of large resorts in prime beach side locations; instead, small clusters of beach fale occupy some of the best coastal sites in Samoa. This also irks some Samoans involved in the tourism industry, as they feel that there are too many run-down beach fale, forming a scar on the landscape. Related to this point, it has been suggested that the development of a strong budget tourism sector is not good for Samoa’s image because a country so well endowed with natural and cultural assets should be home to high class resorts which attract high spending tourists. In addition there is some jealousy of the success of beach fale from the owners of small, lower class hotels, who now see many of their former clientele (such as staff of government agencies) preferring to stay in beach fale; it is likely that this jealousy contributes to negative perceptions of what beach fale have to offer the tourism sector. The Government is now introducing changes which could undermine beach fale tourism in some areas. Firstly, an amendment bill was passed in Parliament in on June 26, 2003, to encourage more foreign investment in higher class resorts. This involves the government playing a stronger role in assisting outsiders to lease land, and tax breaks being given to new hotel/resort developments, with the size of the tax relief being proportional to the size of the hotel/resort. This may see more land moving out of community hands, at least temporarily, in the future, but it is unclear if this is also signaling less government support for the small-scale beach fale initiatives. Secondly, partly in response to concerns from within the tourism industry about supposed substandard accommodation and facilities provided by some beach fale operations, staff of the Samoan Tourism Authority are formalizing planning procedures by developing ‘minimum standards’ which tourist accommodation providers must abide by if they want to be promoted or endorsed by the Government. Depending on the final details of these minimum standards, this may mean that less wealthy families will be unlikely to establish a beach fale venture, as greater resources will be required to meet the minimum standards. Based on these findings and an earlier paper ( 2005b), this working paper makes four key recommendations: • Firstly, village leaders together with Samoan Tourism Authority (STA) personnel need to regularly monitor the development of beach fale (through personal observation, village meetings, and consultation with tourists), and to control this development where necessary, in order to: a) maximise the benefits villagers gain from the fale (for example, in order to maintain their popularity beach fale need to continue to offer tourists a unique cultural experience in a relaxed environment - if some villages are oversubscribed with beach fale enterprises and owners start haggling for custom, this is likely to deter tourists) b) minimise inconvenience/harm to local people from tourism. To date, matai have effectively put in place good social controls on tourist behaviour but they may need to pay more attention to environmental issues (such as sewage disposal and use of fresh water by beach fale), and to equity issues ( ensuring that beach fale development does not impinge heavily on access of local people to the beach or marine resources) otherwise resentment towards tourism could build up over time. • Secondly, the Samoan Tourism Authority and donors such as NZAID should continue to support beach fale enterprises and to ensure that in doing so they offer assistance to a diverse range of enterprises, from the very basic to those that are now well promoted and more up-market. While it would be easy to overlook the basic beach fale enterprises, they effectively provide an important livelihood strategy particularly for those who are not in a strong economic position withintheir village, and it is operators of these enterprises who are in more need of help with matters like publicity, marketing, and service provision. • Thirdly, officials need to recognize the importance of the domestic tourism market, and to encourage development of this market both because a) it is a very good source of revenue and it is less fickle than the international tourism market, and b) this would signal that the government is interested in the recreation and well-being of its own citizens, rather than just offering up the country’s best scenic assets for the enjoyment of foreign tourists. • Fourthly, there is further potential to develop the beach fale sector, but advice needs to be provided to villagers about development of associated products and services, such as beach clothing, souvenirs, food or tours, so that they are aware of viable options which do not just replicate the basic beach fale concept. The Samoan Tourism Authority, Small Business Enterprise Centre, donors and other relevant agencies could assist villagers to identify and develop appropriate products and services to enhance the beach fale experience. In summary, this paper shows how a unique model of tourism development centred on basic beach fale has evolved in Samoa and is reaping considerable benefits for rural people. Samoa has until recently eschewed many advances from international interests because of land tenure issues, preferring to take a path which has supported the development of a strong and dynamic budget beach fale sector (see 2005a, 2005b). This paper suggests that although beach fale tourism does not attract high spending tourists, it should be considered ‘high value’ in terms of community development because most economic benefits are retained locally, it is based upon local skills and resources, it involves cultural education of guests, it supports conservation of resources, and it does this all in the context of high levels of local ownership, participation and control.
Keywords: Samoa; Tourism industry; Fields of Research::360000 Policy and Political Science::360200 Policy and Administration::360201 Public policy